Gambaran Pengetahuan, Sikap, dan Tindakan Pencegahan HIV/AIDS pada Remaja Sekolah SMAN 8 Kota Kupang - Novitasari Novitasari; Yuliana Radja Riwu; Deviarbi Sakke Tira (SEHATMAS: Jurnal Ilmiah Kesehatan Masyarakat, 2025)
Adolescence is a transitional period characterized by physical, psychological, and social changes that have the potential to influence risky behavior, including the transmission of HIV/AIDS. Indonesia continues to experience an increase in HIV/AIDS cases from year to year, with productive age groups, including adolescents, as one of the most vulnerable. Lack of knowledge and low access to information related to HIV/AIDS are factors that contribute to the low awareness of prevention among adolescents. This study aims to determine the description of knowledge, attitudes, and actions to prevent HIV/AIDS among adolescents at SMA Negeri 8 Kupang City using a descriptive design with a cross-sectional approach. The study population was students of SMA Negeri 8 Kupang, with the number of samples determined based on inclusion criteria and using stratified random sampling. The research instrument was a questionnaire that included aspects of knowledge, attitudes, and HIV/AIDS prevention actions, and data were analyzed univariately to describe the frequency distribution of each variable. The results showed that most respondents had knowledge in the moderate category, attitudes that tended to be positive towards HIV/AIDS prevention efforts, but the application of preventive measures in everyday life was still not optimal, indicating a gap between knowledge and real behavior. Suggestions for adolescents include improving knowledge about HIV/AIDS supported by the development of positive attitudes and environmental reinforcement to encourage consistent preventive actions, while school-based health education and the active involvement of health workers are essential in strengthening HIV/AIDS prevention efforts among adolescents.